A reality check on the GARCH-MIDAS volatility models - Nader Virk; Farrukh Javed; Basel Awartani (Örebro University School of Business, 2021)
We employ a battery of model evaluation tests for a broad-set of GARCH-MIDAS models and account for data snooping bias. We document that inferences based on standard tests for GM variance components can be misleading. Our data mining free results show that the gains of macro-variables in forecasting total (long run) variance by GM models are overstated (understated). Estimation of different components of volatility is crucial for designing differentiated investing strategies, risk management plans and pricing of derivative securities. Therefore, researchers and practitioners should be wary of data mining bias, which may contaminate a forecast that may appear statistically validated using robust evaluation tests.
Keywords: C32; C52; G11; G17; 330; GARCH-MIDAS models; component variance forecasts; macro-variables; data snooping